Estimating the costs associated with the management of patients with chronic wounds using linked routine data. Issue 6 (26th March 2015) - Phillips, Ceri J; Humphreys, Ioan; Fletcher, Jacqui; Harding, Keith; Chamberlain, George; Macey, Steven
Abstract: Chronic wounds are known to represent a significant burden to patients and National Health Service (NHS) alike. However, previous attempts to estimate the costs associated with the management of chronic wounds have been based on literature studies or broad estimates derived from incidence rates and extrapolations from relatively small‐scale studies. The aim of this study is therefore to determine the extent of resource utilisation by patients classed as having chronic wounds within Wales using linked routine data – available through the Secure Anonymised Information Linkage (SAIL) database – to estimate the costs associated with the management of these patients by the NHS in Wales. The SAIL database brings together, and anonymously links, a wide range of person‐based data from general practitioner (GP) practices within Wales, which includes primary and secondary care consultations to create an encrypted anonymised linking field for each individual. This linkage allows the patient pathway to be tracked through the NHS system both retrospectively and prospectively from a specific reference date. The estimated costs were derived by extrapolating to an all‐Wales level from the results gleaned from the SAIL database using the respective READ codes to capture relevant patients with chronic wounds. The number of patients identified as having chronic wounds within the SAIL database was 78 090, which equates to 190 463 across Wales as a whole and a prevalence of 6% of the Welsh population. The total cost of managing patients with chronic wounds in Wales amounted to £328·8 million – an average cost of £1727 per patient and 5·5% of total expenditure on the health service in Wales. A relatively few READ codes represented a significant proportion of expenditure, with diabetic foot ulcers, leg ulcers, foot ulcers, varicose eczema, bed sores and postoperative wound care constituting 93% of total expenditure. When a more conservative perspective was used in relation to classification of chronic wounds, the total cost amounted to £303 million. However, these are likely to be underestimates because of the lack of information for patients with treatments lasting over 6 months and not including patients who might have entered the health care system of wound management elsewhere – such as patients contracting pressure ulcers in hospitals and having surgical wound infections.